10.1016/0967-0653(96)83371-0 (CrossRef Listing of Deleted DOIs, 2000)
Background With Türkiye's aging population and widespread internet usage, the excessive seeking of health information through online platforms, formally identified as cyberchondria, has emerged as a concern affecting older individuals' health perception and psychological well-being. Objective This study aimed to evaluate the association of cyberchondria with health perceptions and psychological well-being among older participants in a third-age university program. Methods This cross-sectional study included 352 participants aged ≥60 (mean 67.4, SD 4.7) years from Tazelenme University, Antalya, Türkiye, and was conducted between November and December 2024. Data were collected using the Cyberchondria Severity Scale Short Form (CSS-12), Individual Health Perception Scale, and Psychological Well-Being Scale for Older People (PWBS-OP). Statistical analyses included correlation and multiple regression analyses. Results The mean age of the 352 participants was 67.4 (SD 4.7, range 60-87) years, 38.6% (n=136) were first-year students, 69.6% (n=245) were men, 58.8% (n=207) were married, 48.9% (n=172) were university graduates or above, and 65.1% (n=229) had chronic diseases. Significant negative correlations were found between CSS-12 distress, compulsion, and total scores with both Individual Health Perception Scale and PWBS-OP scores (P<.05). According to the multiple linear regression analysis, the presence of chronic disease was the only significant positive predictor of higher health perception levels (B=2.16, 95% CI 1.721-3.593; P=.003), whereas factors such as age, gender, education level, and CSS-12 total scores did not demonstrate a statistically significant impact (P>.05). Psychological well-being (PWBS-OP) was significantly and positively predicted by age (B=0.22, 95% CI 0.037-0.399; P=.02), marital status (B=1.67, 95% CI 1.064-2.716; P=.002), economic status (B=2.10, 95% CI 1.729-3.464; P=.003), and the thought of having an undiagnosed disease (B=3.38, 95% CI 1.038-5.830; P=.007), whereas it was significantly and negatively predicted by medical examinations in the past year (B=-1.29, 95% CI -2.093 to 0.485; P=.002), undergoing examinations without a physician's recommendation (B=-2.04, 95% CI -3.794 to -0.290; P=.02), searching for health-related topics on the internet (B=-1.26, 95% CI -2.152 to -0.360; P=.006), and CSS-12 total scores (B=-0.13, 95% CI -0.261 to -0.060; P=.04). Conclusions High cyberchondria levels significantly impair older adults' psychological well-being and health perception. While demographic factors positively influence health perception, excessive internet-based health seeking deteriorates psychological well-being. Digital health literacy programs, professional online health counseling, and psychological support should be recommended to target cyberchondria risks in older populations.